2020
DOI: 10.1007/s43452-020-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on applicability of two modal identification techniques in irrelevant cases

Abstract: Study on applicability of two modal identification techniques in irrelevant cases is made in this paper. The following techniques are considered: peak picking based on correlation analysis (PP-CA), dedicated for ambient vibrations and eigensystem realization algorithm (ERA), formulated for free-decay vibrations investigation. Irrelevant cases are found when analyzed signals are different than recommended to a given technique. The study is conducted on examples of two real structures: masonry tower and steel ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The damping ratios cannot be identified, which is the method’s limitation. The practical applications of the PP-CA technique are addressed in, e.g., [ 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The damping ratios cannot be identified, which is the method’s limitation. The practical applications of the PP-CA technique are addressed in, e.g., [ 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Directly measured, short-time free-decay signals caused by blasts of wind or river undulations are considered as the input. A similar approach was applied in the paper [ 11 ], in which the ERA efficacy in the case of a massive masonry tower was studied.…”
Section: Methodsmentioning
confidence: 99%
“…However, the peak of the frequency response shown in Figure 21 may not exactly correspond to the natural frequency. Therefore, the Eigensystem Realization Algorithm (ERA) [38] is used to calculate the natural frequencies of each virtual structure, which are shown in Table 7. Via ERA, structural modal information can be solved by impulse response.…”
Section: Natural Frequencies Estimation Of the Virtual Structuralmentioning
confidence: 99%
“…The first of them was based on the correlation between input data, excitations; and output data, responses of the structure [34][35][36]. The second one, called the operational modal analysis (OMA) or ambient modal analysis, was based solely on output data [37][38][39]. There are many methods for the identification of dynamic parameters of structures.…”
Section: Introductionmentioning
confidence: 99%
“…A good review of the literature on modal identification techniques can be found in [39,45,46]. Furthermore, in the literature [38,39,[47][48][49], a comparison of the dynamic parameters identification carried out by various methods could be found.…”
Section: Introductionmentioning
confidence: 99%